Compulsory measures of educational influence applied to minors who have committed acts prohibited by criminal law: a comparative study of the Kazakh-Russian experience - Talan, М.В.; Nagornov, К.И. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2022)
In this paper, the readers are presented with the results of a comparative study of the Kazakh-Russian experience in terms of the legal regulation of compulsory measures of educational influence imposed on minors who have committed acts prohibited by criminal law. Based on the analysis of the provisions of criminal legislation and explanations of the highest judicial instances of the Soviet and post-Soviet periods, the article describes the types, grounds and conditions, the procedure for the application of compulsory education measures in the two states, defines their common and distinctive features, as well as disadvantages and advantages. The objectives of the study were to assess the development of legal provisions in the studied part, as well as to determine the most optimal and effective model for describing coercive measures of educational influence in criminal law. Based on the results of the study, conclusions were formulated aimed at improving the criminal legal basis of compulsory measures of educational influence in Kazakhstan and Russia.